Analytical Study of Three Liquid Crystals Used as Stationary Phases in Gas Chromatography - BENALIA, M.; BADJAH-HADJ-AHMED, A.Y.; DJEDID, M.; MEKLATI, B.Y.; AL-DUJAILI, A.H. (Asian Journal of Chemistry, 2010)
The investigation of the analytical properties of three liquid crystals 5-(4-methoxyphenyl)-azophenyl)-2-butylthio-1,3,4- oxadiazole (phase I), 5-(4-(carboxymethylphenyl)-azophenyl)- 2-butyl-thio-1,3,4-oxadiazole (phase II) and 5-(4- (propoxyphenyl)-azophenyl)-2-butyl thio-1,3,4-oxadiazole (phase III) was carried out by gas chromatography using glass capillary columns. For this purpose, 79 solutes belonging to various families were injected. Among these compounds which have different polarities and volatilities, we studied the retention of 16 alkylbenzenes, 7 polar substituted benzenes, 24 polar and non-polar phenols, 12 substituted naphthalenes and 20 constituents of natural products. Comparison of the retention data of the studied components has shown that phase II allowed a better separation than the other phases. The three liquid crystalline materials show a good separation of the studied isomers except for xylene.